2016
DOI: 10.1007/s10518-016-9946-z
|View full text |Cite
|
Sign up to set email alerts
|

Linking of adjacent three-storey buildings for mitigation of structural pounding during earthquakes

Abstract: The reports after major earthquakes indicate that the earthquake-induced pounding between insufficiently separated buildings may lead to significant damage or even total collapse of structures. An intensive study has recently been carried out on mitigation of pounding hazards so as to minimize the structural damages or prevent collisions at all. The aim of this paper is to investigate the effectiveness of the method when two adjacent three-storey buildings with different (substantially different) dynamic prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 46 publications
0
39
0
4
Order By: Relevance
“…Recent works on the seismic response of adjacent structures include nonlinear dynamical models for pounding events [2][3][4][5], stochastic assessment of pounding risk [6], structural analysis of large buildings connected by sky-bridge links [7], seismic response of adjacent nonstructural components [8], and reduced-order models for the study of the analytical characteristics of linked structures [9][10][11][12]. Also, a wide variety of control strategies has been recently proposed, including passive linking systems with viscous and viscoelastic elements [13][14][15][16][17][18], nonlinear linking dampers [19,20], semiactive magnetorheological linking dampers [21][22][23], shared Tuned-Mass-Dampers [24][25][26], and active linking devices [27,28]. Improved performance and robustness can be attained by hybrid control schemes that make a combined use of interbuilding linking elements and vibration control systems implemented in the individual buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works on the seismic response of adjacent structures include nonlinear dynamical models for pounding events [2][3][4][5], stochastic assessment of pounding risk [6], structural analysis of large buildings connected by sky-bridge links [7], seismic response of adjacent nonstructural components [8], and reduced-order models for the study of the analytical characteristics of linked structures [9][10][11][12]. Also, a wide variety of control strategies has been recently proposed, including passive linking systems with viscous and viscoelastic elements [13][14][15][16][17][18], nonlinear linking dampers [19,20], semiactive magnetorheological linking dampers [21][22][23], shared Tuned-Mass-Dampers [24][25][26], and active linking devices [27,28]. Improved performance and robustness can be attained by hybrid control schemes that make a combined use of interbuilding linking elements and vibration control systems implemented in the individual buildings.…”
Section: Introductionmentioning
confidence: 99%
“…More destructive dynamic loads, including earthquakes (Jankowski and Mahmoud 2015, Naderpour et al 2016, may also occur in our country (see Fig. 1), although their frequency of occurrence is relatively low.…”
Section: Fig 1 Seismic Hazard Map Of Northern Europementioning
confidence: 85%
“…[1,3,8,[22][23][24]). Mostly pounding elements with a linear or a nonlinear spring damper system, following the Hertz law, are applied (cf.…”
Section: Methods Of Contact Constraint Enforcementmentioning
confidence: 99%
“…It has been observed that the motion of buildings due to earthquake excitation may not cause as much damage to buildings as the result of possible pounding between them [1][2][3][4]. Pounding occurs if the separation distance between adjacent buildings is not sufficient in order to compensate for their relative movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation